Pembinaan Keagamaan dalam Membangun Karakter Siswa di Sekolah Menengah Pertama (SMP) PGRI Pulau Salemo Kab. Pangkep - Hamka; Hakim, Ahmad; Shamad, Ishaq (Journal of Gurutta Education, 2023)
This research is about Religious Guidance in Building Students' Character in Junior High School (SMP) PGRI Salemo Island Kab. This study uses a qualitative descriptive type of research because the data used is qualitative, namely regarding the methods and implementation of student character education carried out by the parties at SMP PGRI Salemo Island. Data and information collection is done by field research (field research) with interview, observation, and documentation techniques. The results showed that the religious development of students at SMP PGRI Salemo Island Kab. Pangkep is first through habituation activities, examples from educators, character education in every lesson, giving advice and motivation, and extracurricular activities. Then, in fostering the character of students, they have shown good results in changing the character of students. Students already have religious, honest, and disciplined characteristics. Students' responsibilities are also able to perform obligatory prayers, sunnah prayers, remembrance of reading the Koran, and some are even able to memorize some verses of the Qur'an. The results of the study concluded that the steps and efforts made by educators, especially teachers, proved to be very effective in building the noble character of students at SMP PGRI Pulau Salemo Kab. Pangkep